1990
DOI: 10.1007/bf00154641
|View full text |Cite
|
Sign up to set email alerts
|

Gender-fair psychotherapy in the United States: A possible dream?

Abstract: Since Freud's era, women have been counseling and psychotherapy's largest consumers. White Freud talked and wrote almost exclusively about men, his patients were primarily women. This practice of treating women as patients, while perceiving men as the prevailing standard for percept and practice has resulted in the largely androcentric or mate-determined psychology of human behavior which we have today (Denmark, 1980;Hare-Mustin, 1983).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Earlier research demonstrated the existence of gender-role stereotyping by therapists and counselors in training (Aslin, 1977;Broverman, Broverman, Clarkson, Rosenkrantz, & Vogel 1970;Dreman, 1978;Hampton, Lambert, & Snell, 1986). Both male and female therapists have been found to associate unique beliefs with women's and men's mental health (Maslin & Davis, 1975;Tanney & Birk, 1976) and perpetuate traditional gender-role socialization in therapy (APA, 1975;Nickerson & Kremgold-Barrett, 1990). Analogue studies (Abramowitz et al, 1975;Crosby & Sprock, 2004;Seem & Johnson, 1998;Thomas & Stewart, 1971) as well as studies of actual therapists and patients (Bingham & House, 1973;Pietrofesa & Schlossberg, 1970), demonstrate counselor bias against female clients entering nontraditional careers, displaying nontraditional gender-role behavior, or displaying problem behaviors (e.g., antisocial symptoms) that are inconsistent with traditional gender-role expectations.…”
mentioning
confidence: 99%
“…Earlier research demonstrated the existence of gender-role stereotyping by therapists and counselors in training (Aslin, 1977;Broverman, Broverman, Clarkson, Rosenkrantz, & Vogel 1970;Dreman, 1978;Hampton, Lambert, & Snell, 1986). Both male and female therapists have been found to associate unique beliefs with women's and men's mental health (Maslin & Davis, 1975;Tanney & Birk, 1976) and perpetuate traditional gender-role socialization in therapy (APA, 1975;Nickerson & Kremgold-Barrett, 1990). Analogue studies (Abramowitz et al, 1975;Crosby & Sprock, 2004;Seem & Johnson, 1998;Thomas & Stewart, 1971) as well as studies of actual therapists and patients (Bingham & House, 1973;Pietrofesa & Schlossberg, 1970), demonstrate counselor bias against female clients entering nontraditional careers, displaying nontraditional gender-role behavior, or displaying problem behaviors (e.g., antisocial symptoms) that are inconsistent with traditional gender-role expectations.…”
mentioning
confidence: 99%